2015
DOI: 10.1163/1568539x-00003281
|View full text |Cite
|
Sign up to set email alerts
|

Mate detection and seasonal variation in stick insect mating behaviour (Phamatodea: Clitarchus hookeri)

Abstract: For animals that exhibit a scramble competition mating system, sexual selection pressures on mate searching ability are expected to be strong. Scramble competition mating systems evolve when populations provide females with equal accessibility to all male competitors, yet sex ratio and population density influences mating systems and varies seasonally. The stick insect species,Clitarchus hookeri, is frequently found in copula, yet very little is known about it’s mating behaviour. We preformed behavioural tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…In the phylogeny, OBP1 is closely clustered with the two Z. nevadensis PBPs ( OBP1 and OBP2 ) ( Fig 5 ), indicating the C. hookeri OBP1 is most likely a PBP. A recent study has demonstrated that male C. hookeri detects females using airborne chemical cues, most likely pheromones emitted by the females [ 7 ]. The presence of a higher density of basiconic sensilla on male than female antennae further indicates that males are responsible for long range pheromone reception [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the phylogeny, OBP1 is closely clustered with the two Z. nevadensis PBPs ( OBP1 and OBP2 ) ( Fig 5 ), indicating the C. hookeri OBP1 is most likely a PBP. A recent study has demonstrated that male C. hookeri detects females using airborne chemical cues, most likely pheromones emitted by the females [ 7 ]. The presence of a higher density of basiconic sensilla on male than female antennae further indicates that males are responsible for long range pheromone reception [ 7 ].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study has demonstrated that male C. hookeri detects females using airborne chemical cues, most likely pheromones emitted by the females [ 7 ]. The presence of a higher density of basiconic sensilla on male than female antennae further indicates that males are responsible for long range pheromone reception [ 7 ]. Therefore, a high abundance of a PBP transcript in a C. hookeri female antennae seems unexpected.…”
Section: Resultsmentioning
confidence: 99%
“…In New Zealand, most northern populations of the common diploid stick insect C. hookeri have an even sex ratio and all reproduction is assumed to be sexual (Langton‐Myers, Holwell, & Buckley, ; Morgan‐Richards, Trewick, & Stringer, ; Myers, Buckley, & Holwell, ; Myers, Holwell, & Buckley, ), but males are absent from many southern locations (Figure ). A widespread parthenogenetic lineage appears to have resulted from range expansion by a single mtDNA lineage (Buckley, Marske, & Attanayake, ; Morgan‐Richards et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In New Zealand, most northern populations of the common diploid stick insect C. hookeri have an even sex ratio and all reproduction is assumed to be sexual (Langton- Myers, Holwell, & Buckley, 2019;Morgan-Richards, Trewick, & Stringer, 2010;Myers, Buckley, & Holwell, 2015;Myers, Holwell, & Buckley, 2017), but males are absent from many southern locations ( Figure 1 (Buckley, Marske, & Attanayake, 2010;Morgan-Richards et al, 2010). Throughout the southern and eastern North Island and eastern South Island of New Zealand ( Figure 2), reproduction is inferred to be entirely parthenogenetic (Wu, Twort, Crowhurst, Newcomb, & Buckley, 2017); males have been recorded only sporadically and at very low density (Buckley et al, 2010;Morgan-Richards et al, 2010).…”
mentioning
confidence: 99%
“…that are among the first native plants to colonize cleared land (Dawson & Lucas, 2000). At night C. hookeri males are very mobile while females tend to remain inactive up until their first mating opportunity (Myers et al, 2015). Therefore, populations of Clitarchus species likely have the ability to quickly expand their distributions, increasing their chances of inter-species interactions.…”
Section: Introductionmentioning
confidence: 99%